Positive electrode material, method for preparing the same, and battery

CN120565603BActive Publication Date: 2026-10-27JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510486985.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2026-10-27
Estimated Expiration
2045-04-17

AI Technical Summary

Technical Problem

然而,O3型层状氧化物仍然有一些问题亟待解决

Benefits of technology

[0034]在本申请实施例中,所提供的正极材料为适用于钠离子电池的正极材料,该正极材料具有核壳结构,且内核为钠离子正极材料,外壳包括了包含硅酸钠的第一包覆层以及包含硅酸铋的第二包覆层。由此,通过使硅酸钠包覆在钠离子正极材料的表面,可以降低材料表面的残碱,降低pH,改善后续由于高pH带来的加工问题,而且硅酸钠具有一定的导电性(电导率为10-6S.cm-1),可增强正极材料的导电性;进一步,通过硅酸铋包覆层的设置,利用硅酸铋涂层具有较大的比表面积的特点,不仅能提供一些活性位点,提高电化学活性;而且其还具有一定的柔韧性,硅酸铋的存在可使得在钠离子嵌入和脱出时体积膨胀小,使其产生的内应力小,避颗粒微裂纹的产生,从而保证颗粒完整性,保证循环性能。从而,该具有双功能层的正极材料能实现长循环性能,具备良好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120565603B_ABST
    Figure CN120565603B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a positive electrode material, a preparation method thereof and a battery. The provided positive electrode material comprises a core, a first coating layer coated on at least part of the surface of the core, and a second coating layer coated on at least part of the surface of the first coating layer; the core comprises a sodium ion positive electrode material; the first coating layer comprises sodium silicate; and the second coating layer comprises bismuth silicate. A positive electrode sheet comprises the provided positive electrode material. A battery comprises the provided positive electrode sheet. The application can reduce the residual alkali content of the positive electrode material in a sodium ion battery, improve the conductivity and dynamic performance of the positive electrode material, and make the positive electrode material exhibit good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a cathode material, its preparation method, and a battery. Background Technology

[0002] In recent years, the rapid development of the electric vehicle market and the increasing demand for energy storage have made it difficult for lithium resources to meet market demand. However, sodium-ion batteries have attracted significant attention due to their low cost, abundant raw materials, and safety performance. Cathode materials, as a crucial component of sodium-ion batteries, play a key role in improving energy density. Therefore, developing materials with high energy density, low cost, long cycle life, and air stability is essential. Currently, sodium-ion battery cathode materials mainly include layered oxides, Prussian blue compounds, polyanionic compounds, and organic compounds. Among these, sodium-ion layered oxides have certain advantages in terms of energy density, mass production processes, and cost control.

[0003] Sodium-ion layered cathode oxides are mainly classified into P2-type oxides and O3-type oxides. Among them, O3-type cathode materials have a higher initial sodium content, thus offering higher reversible capacity and are favored by researchers. However, O3-type layered oxides still have some problems to be solved. For example, O3-type layered oxides suffer from poor air stability. During synthesis and storage, exposure to air results in the formation of a large amount of residual alkali on the surface. This is mainly because air has a certain humidity, and the moisture in the air undergoes an ion exchange process with the sodium ions within the material, causing sodium ions (Na+) to... + It reacts with carbon dioxide in the air to produce impurities such as sodium carbonate. Furthermore, because Na... + The radius is relatively large, and with Na + When sodium ions are extracted, the sodium layer exhibits an ordered arrangement of sodium vacancies. Under high voltage, the layered structure loses its electrostatic shielding effect, leading to phase transitions and slippage. This makes it difficult to maintain the layered structure, resulting in volume expansion or lattice distortion, which in turn significantly reduces battery safety and deteriorates electrochemical reaction performance. Therefore, reducing the residual alkali content of sodium-ion battery cathode materials is a problem that must be improved or solved in the industrialization of sodium-ion batteries. Summary of the Invention

[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a cathode material, a method for preparing the same, and a battery, which can reduce the residual alkali content of the cathode material in sodium-ion batteries, enabling the cathode material to exhibit good electrochemical performance.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows:

[0006] According to a first aspect of this application, this application provides a cathode material, the cathode material comprising a core, a first coating layer covering at least a portion of the surface of the core, and a second coating layer covering at least a portion of the surface of the first coating layer;

[0007] The core includes a sodium ion cathode material;

[0008] The first coating layer includes sodium silicate;

[0009] The second coating layer comprises bismuth silicate.

[0010] In some embodiments, the first coating layer comprises a plurality of granular sodium silicate.

[0011] In some embodiments, the second coating layer comprises a thin film of bismuth silicate.

[0012] In some of these embodiments, the thickness of the first coating layer is 20 nm to 50 nm.

[0013] In some of these embodiments, the thickness of the second coating layer is 50 nm to 120 nm.

[0014] In some embodiments, the sodium silicate has the chemical formula Na. a Si b O c Where 1≤a≤4, 1≤b≤4, and c satisfies Na a Si b O c The charge balance.

[0015] In some of these embodiments, the bismuth silicate has the chemical formula Bi. d Si e O f Where 2≤d≤12, 1≤e≤5, and f satisfies Bi d Si e O f The charge balance.

[0016] In some embodiments, the chemical formula of the sodium ion cathode material is Na. x TMO2,TM includes at least two of the transition metals Ni, Co, Mn, Cu, Fe or Ti, and 0.6≤x≤1.

[0017] In some embodiments, the particle size D50 of the core sodium ion cathode material is 0.5 μm to 10 μm.

[0018] According to a second aspect of this application, this application provides a method for preparing a positive electrode material, the method comprising the following steps:

[0019] Sodium-ion cathode material and silicon-containing compound are mixed and reacted to obtain intermediate material;

[0020] The intermediate material is subjected to a first-stage sintering process to obtain a sodium-ion cathode material coated with sodium silicate.

[0021] The sodium-ion cathode material coated with sodium silicate is mixed with a bismuth-containing compound and then sintered in a second stage. The sintering temperature of the first stage is lower than that of the second stage to obtain the cathode material.

[0022] The cathode material includes a core, a first coating layer covering at least a portion of the surface of the core, and a second coating layer covering at least a portion of the surface of the first coating layer; the core includes a sodium ion cathode material; the first coating layer includes sodium silicate; and the second coating layer includes bismuth silicate.

[0023] In some of these embodiments, the sintering temperature of the first stage sintering is 450°C to 525°C.

[0024] In some of these embodiments, the holding time for the first stage sintering is 2 to 4 hours.

[0025] In some of these embodiments, the sintering temperature for the second stage sintering is 550°C to 650°C.

[0026] In some of these embodiments, the holding time for the second stage sintering is 4 to 8 hours.

[0027] In some of these embodiments, the step of obtaining the intermediate material specifically includes:

[0028] A sodium-ion cathode material is provided; a silicon-containing compound and a resin are mixed, the pH is adjusted, and the mixture is heated and stirred. After separation, washing and drying, a coated precursor material is obtained; the sodium-ion cathode material, the coated precursor material and a complexing agent are mixed, reacted, washed and dried, and the intermediate material is obtained.

[0029] In some of these embodiments, the preparation method satisfies at least one of the following features (1) to (11):

[0030] (1) The sodium-ion cathode material is provided by: mixing a sodium-containing compound and a transition metal oxide by ball milling to obtain a mixed material, pre-sintering the mixed material at a temperature of 300℃~525℃ for 6h~10h, and then sintering it at a temperature of 525℃~600℃ for 10h~16h to obtain the sodium-ion cathode material; (2) The silicon-containing compound includes at least one of tetraethyl orthosilicate, methyl orthosilicate or isopropyl orthosilicate; (3) The resin includes phenolic resin; (4) The bismuth-containing compound includes at least one of bismuth nitrate, bismuth sulfate, bismuth chloride, bismuth acetate or bismuth citrate; (5) The volume ratio of the silicon-containing compound to the resin is 1:1~1:1. 0; (6) The molar ratio of the bismuth-containing compound to the silicon-containing compound is 1:1.5 to 1:4; (7) The pH adjustment includes adjusting the pH value to 3 to 5 by acid solution; (8) The heating temperature and stirring time are 50℃ to 70℃ and 6h to 8h; (9) The complexing agent includes at least one of citric acid, tartaric acid, maleic acid, oxalic acid or ethanolamine; (10) The rotation speed of the sodium ion cathode material, the coating precursor material and the complexing agent is 400 to 600 r / min and the mixing time is 10min to 60min; (11) The reaction temperature is 80℃ to 100℃ and the reaction time is 3h to 5h.

[0031] According to a third aspect of this application, this application provides a positive electrode sheet, which includes a current collector and a positive electrode active material layer disposed on the surface of the current collector; the positive electrode active material layer includes the aforementioned positive electrode material, or includes a positive electrode material prepared by the aforementioned method.

[0032] According to a fourth aspect of this application, this application provides a battery comprising a negative electrode and the aforementioned positive electrode.

[0033] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0034] In this embodiment, the provided cathode material is suitable for sodium-ion batteries. This cathode material has a core-shell structure, with the core being a sodium-ion cathode material and the outer shell comprising a first coating layer containing sodium silicate and a second coating layer containing bismuth silicate. Therefore, by coating the surface of the sodium-ion cathode material with sodium silicate, residual alkali on the material surface can be reduced, the pH can be lowered, and subsequent processing problems caused by high pH can be improved. Furthermore, sodium silicate has a certain degree of conductivity (10⁻⁶). -6 S.cm -1This process enhances the conductivity of the cathode material. Furthermore, the bismuth silicate coating, with its large specific surface area, not only provides active sites and improves electrochemical activity, but also exhibits flexibility. The presence of bismuth silicate minimizes volume expansion during sodium ion insertion and extraction, reducing internal stress and preventing microcracks in the particles, thus ensuring particle integrity and cycle performance. Therefore, this cathode material with a dual-functional layer achieves long cycle life and shows promising application prospects.

[0035] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0036] Figure 1 The diagram shown is a structural schematic of a positive electrode material provided in an embodiment of the present invention;

[0037] Figure 2 The image shown is a SEM image of the sodium ion cathode material (core) provided in Example 1 of this invention;

[0038] Figure 3 The image shown is a SEM image of the cathode material provided in Embodiment 1 of the present invention.

[0039] Explanation of reference numerals in the attached figures:

[0040] 10-Sodium ion cathode material;

[0041] 20 - First coating layer;

[0042] 30 - Second coating layer. Detailed Implementation

[0043] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0044] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0045] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.

[0046] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0047] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0048] Research on sodium-ion batteries has developed rapidly in recent years. As analyzed in the background section, current sodium-ion battery cathode materials, such as O3-type cathode materials, still suffer from poor air stability; during synthesis and storage, exposure to air results in the formation of large amounts of residual alkali on the surface. Furthermore, due to the inherent limitations of Na... +The ionic radius is relatively large, and there is also the problem of easy volume expansion or lattice distortion. In related technologies, it is difficult to deal with the above two problems by a single method. For example, the treatment process for residual alkali is generally divided into the following types: The first method is water washing process (such as the process disclosed in CN112290014A). Although this water washing process can remove most of the residual alkali, the water washing process is complicated and wastes a lot of water resources. The waste liquid after washing also needs to be recycled and cleaned, and the material needs to be dried, which consumes a lot of energy. Moreover, the material after water washing and drying is more sensitive to moisture, which increases the energy storage cost. The second approach utilizes the principle of acid-base neutralization, typically involving the introduction of acidic gas or the washing and reaction with an acidic solution during sintering (as disclosed in CN108878863A). However, this acid-based treatment method presents significant problems, particularly the generation of excess acidic waste liquid or gas, which can corrode equipment and is environmentally unfriendly. Furthermore, the use of acidic solutions may lead to the dissolution of small amounts of transition metal ions, causing performance degradation such as capacity reduction, making industrialization difficult. Moreover, the specific functional layer reaction with residual alkali (as disclosed in CN112864372A) requires the distributed addition and control of the binary functional layer, as well as the determination of whether the precipitate is an effective precipitate standard. This process is cumbersome, hindering large-scale production and making it impossible to precisely control the thickness of a specific functional layer. Furthermore, in related technologies, doping is commonly used to address issues such as lattice distortion or large charge-discharge volume changes. Doping is applied to transition metal or alkali metal layers, and the effects vary depending on the doping or substitution location, thereby improving structural stability and cycle performance. This has become a common method for optimizing material dynamics. Therefore, it is crucial to provide a technical approach that can simultaneously alleviate both of these problems.

[0049] In view of this, the inventors of this application, from the perspective of improving the performance of sodium-ion battery cathode materials, and through in-depth research, have discovered and proposed improvements to existing sodium-ion battery cathode materials and their preparation methods, in order to optimize the structure of sodium-ion battery cathode materials, alleviate the problems of high residual alkali content and lattice distortion / volume expansion in existing sodium-ion cathode materials, and thereby improve the cycle performance and specific capacity and other electrochemical performance of sodium-ion batteries using this cathode material. The following is a detailed description of this application.

[0050] [Cathode Material]

[0051] like Figure 1 As shown, in some embodiments, a positive electrode material is provided, the positive electrode material including a core, a first coating layer 20 covering at least a portion of the surface of the core, and a second coating layer 30 covering at least a portion of the surface of the first coating layer 20;

[0052] The core includes sodium-ion cathode material 10;

[0053] The first coating layer 20 includes sodium silicate;

[0054] The second coating layer 30 includes bismuth silicate.

[0055] Optionally, the provided cathode material can be a sodium-ion battery cathode material; further, the cathode material can be a sodium-ion battery layered oxide cathode material.

[0056] It should be noted that, in this application, the term "coating" is not limited to direct coating, but also includes indirect coating. For example, when the first coating layer 20 coats the sodium-ion cathode material 10, there may be no other structure between the first coating layer 20 and the outer surface of the sodium-ion cathode material 10, or there may be one or more other structures between the first coating layer 20 and the outer surface of the sodium-ion cathode material 10. Preferably, there are no other structures between the first coating layer 20 and the outer surface of the sodium-ion cathode material 10. Similarly, when the second coating layer 30 coats the first coating layer 20, there may be no other structure between the second coating layer 30 and the outer surface of the first coating layer 20, or there may be one or more other structures between the second coating layer 30 and the outer surface of the first coating layer 20.

[0057] The first coating layer 20 is formed or coated on at least a portion of the surface of the core sodium-ion cathode material 10, which can protect or improve the sodium-ion cathode material 10, reduce residual alkali content, and optimize the conductivity of the cathode material. The first coating layer 20 being formed on at least a portion of the surface of the core sodium-ion cathode material 10 means that the first coating layer 20 can completely encapsulate the core sodium-ion cathode material 10 within the first coating layer 20, or it can be that the first coating layer 20 only coats a portion of the outer surface of the core sodium-ion cathode material 10; that is, the first coating layer 20 can completely coat the core sodium-ion cathode material 10, or it can coat a portion of the surface of the core sodium-ion cathode material 10. Optionally, in this application, the first coating layer 20 coats a portion of the surface of the core sodium-ion cathode material 10.

[0058] The second coating layer 30 is formed or covers at least a portion of the surface of the first coating layer 20. It can protect the core sodium ion cathode material 10 and the first coating layer 20, suppress volume expansion, prevent lattice distortion from causing microcracks in the stress bands within the particles, enhance the conductivity of the cathode material, ensure interface stability, and thus enhance the electrochemical performance of the cathode material. The second coating layer 30 being formed on at least a portion of the surface of the first coating layer 20 means that the second coating layer 30 can completely encapsulate the first coating layer 20 within the second coating layer 30, or it can be that the second coating layer 30 only covers a portion of the outer surface of the first coating layer 20; that is, the second coating layer 30 can completely cover the first coating layer 20, or it can cover a portion of the surface of the first coating layer 20, preferably completely covering it.

[0059] The provided cathode material has a core-shell structure, where the core uses a traditional sodium-ion battery cathode material, and the outer shell or shell layer includes a first coating layer 20 and a second coating layer 30. The first coating layer 20 can be a sodium silicate ion conductor coating generated by reacting residual alkali on the surface of the sodium-ion battery cathode material, and the second coating layer 30 can be a bismuth silicate coating. In this embodiment, the first coating layer 20 can be a sodium silicate coating generated by reacting residual alkali on the surface of the sodium-ion cathode material 10 with silicon material. This not only reduces residual alkali on the material surface and lowers the pH, improving subsequent processing problems caused by high pH, ​​but also provides excellent protection or improvement for the core sodium-ion cathode material 10. Furthermore, sodium silicate has a certain conductivity (10⁻⁶). -6 S.cm -1 This enhances the conductivity of the cathode material. Furthermore, the second coating layer 30 is a bismuth silicate coating, which protects the core sodium-ion cathode material 10 and the first coating layer 20. In particular, the bismuth silicate coating has a large specific surface area, providing not only active sites and improving electrochemical activity, but also a certain degree of flexibility (e.g., bismuth silicate with thin-film properties). The presence of bismuth silicate minimizes volume expansion during sodium ion insertion and extraction, reducing internal stress and preventing microcracks in the particles, thus ensuring particle integrity and cycle performance.

[0060] Therefore, by sequentially depositing a first coating layer 20 and a second coating layer 30 on the surface of the sodium-ion cathode material 10, a multi-layer coating structure is adopted, which can effectively provide excellent protection or modification for the sodium-ion cathode material 10. This not only consumes harmful substances (such as residual alkali), improves processing and storage, enhances conductivity, inhibits or slows down volume expansion, and prevents microcracks caused by lattice distortion in the stress bands within the particles, but the second coating layer 30 also has high conductivity, which can improve kinetic performance. In addition, the presence of this multi-layer coating structure can ensure interface stability, thereby achieving long-cycle performance of the cathode material.

[0061] Through in-depth research, the inventors have discovered that, in addition to meeting the above-mentioned design conditions, the cathode material of this application can further improve its performance if it can optionally meet one or more of the following conditions.

[0062] In this embodiment of the invention, the cathode material is a cathode material with high stability and good electrochemical performance, which may be composed of sodium ion cathode material 10, a first coating layer 20 disposed on the surface of sodium ion cathode material 10, and a second coating layer 30 disposed on the surface of the first coating layer 20.

[0063] In some embodiments, the sodium ion cathode material 10 has the chemical formula Na. x TMO2, wherein TM includes a transition metal, which includes, but is not limited to, at least two of Ni, Co, Mn, Cu, Fe or Ti, and 0.6 ≤ x ≤ 1. For example, x can be 0.6, 0.7, 0.8, 0.9, 1, etc.

[0064] As an example, TM can be selected from Ni and Mn, or TM can be selected from Ni, Mn and Cu, or TM can be selected from Ni, Mn and Fe, or TM can be selected from Ni, Mn and Ti, or TM can be selected from Ni, Fe and Cu, etc.

[0065] Typical, but not limiting, sodium-ion cathode material 10 has the chemical formula Na. x Ni y Mn z O2, where 0.6≤x≤1, 0.1≤y≤0.9, 0.1≤z≤0.9, and y+z=1. For example, the sodium-ion cathode material 10 can be NaNi. 0.5 Mn 0.5 O2, of course, is not limited to this. In practical applications, different sodium nickel manganate cathode materials can be generated according to different stoichiometric ratios of nickel and manganese.

[0066] The selected sodium-ion cathode material 10 has a high theoretical charge specific capacity, and the actual capacity that cathode materials containing it can provide is also high, which helps to improve the battery capacity. In addition, the selected sodium-ion cathode material 10 is beneficial to improving the battery's cycle performance, energy density, and other performance characteristics.

[0067] In some embodiments, the first coating layer 20 comprises a plurality of granular sodium silicate.

[0068] In some embodiments, the second coating layer 30 comprises a thin film of bismuth silicate.

[0069] In this application, the first coating layer 20 can be formed by coating the surface of a single particle with residual alkali on the surface of the sodium ion positive electrode material 10 particles. Therefore, the first coating layer 20 can be a coating layer formed by multiple granular sodium silicate particles, i.e., a sodium silicate coating. Thus, unlike the shape, structure, or composition characteristics of traditional (thin film) coating layers, this first coating layer 20 is a sodium silicate ion-conducting layer, and is a sodium silicate ion-conducting coating generated by reacting with residual alkali on the material surface. The first coating layer 20 coats the surface of the material particles, which not only reduces the residual alkali content on the material surface and lowers the pH, but also has a certain degree of conductivity.

[0070] The second coating layer 30 is a bismuth silicate layer with thin-film properties, which coats the aggregates between particles. The thin-film bismuth silicate has a certain degree of flexibility. The presence of bismuth silicate can minimize the volume expansion during sodium ion insertion and extraction, thereby reducing the internal stress generated and preventing the generation of microcracks in the particles, thus ensuring particle integrity and cycling performance.

[0071] In some embodiments, sodium silicate has the chemical formula Na. a Si b O c Where 1≤a≤4, 1≤b≤4, and c satisfies Na a Si b O c The charge balance. As an example, a = 2, b = 1, c = 3, sodium silicate can be Na2SiO3.

[0072] For example, the first coating layer 20 mentioned above includes Na2SiO3, and the formation of Na2SiO3 from residual alkali Na2CO3 can be shown by the following equation. The reaction equation is as follows:

[0073] SiO2 + Na2CO3 = Na2SiO3 + CO2.

[0074] In some embodiments, the chemical formula of bismuth silicate is Bi. d Si e O f Where 2≤d≤12, 1≤e≤5, and f satisfies Bi d Si e O f The charge balance. As an example, d = 2, e = 1, f = 5, bismuth silicate can be Bi2SiO5.

[0075] By applying the aforementioned thin-film bismuth silicate coating to the surface of the cathode material, not only can electrochemical activity be improved, volume expansion reduced, or lattice distortion prevented from causing microcracks in the stress bands within the particles, but the cathode material can also be effectively isolated from external water or air, which is more conducive to improving the stability of sodium-ion cathode materials in air. Furthermore, it can reduce contact with the electrolyte during cycling and avoid the problem of low cycle capacity retention caused by electrolyte erosion.

[0076] In some embodiments, the thickness of the first coating layer 20 is 20 nm to 50 nm. As an example, the thickness of the first coating layer 20 can be any one of 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm, or a range between any two.

[0077] This application, by controlling the thickness of the first coating layer 20 within a suitable range, can improve the compaction density and conductivity of the cathode material while ensuring that the cathode material maintains a high sodium-ion conductivity, and reduce the residual alkali content on the material surface, thereby increasing the battery's discharge capacity and extending its service life. If the thickness of the first coating layer 20 is too low, such as less than 20 nm, it will not be able to effectively exert the modification effect of the first coating layer 20, and will not be able to effectively reduce the residual alkali on the material surface, resulting in little improvement in cycle performance; if the coating layer thickness is too high, such as greater than 50 nm, the capacity, rate capability, and cycle performance will actually decrease. Therefore, the thickness of the first coating layer 20 needs to be set reasonably.

[0078] In some embodiments, the thickness of the second coating layer 30 is 50 nm to 120 nm. As an example, the thickness of the second coating layer 30 can be any one of 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, and 120 nm, or a range between any two.

[0079] This application, by controlling the thickness of the second coating layer 30 within a suitable range, can improve the compaction density and conductivity of the cathode material while ensuring high sodium-ion conductivity, thereby enhancing electrochemical activity, maintaining particle integrity, and ultimately increasing the battery's discharge capacity and extending its lifespan. If the thickness of the second coating layer 30 is too low, such as less than 50 nm, it will not effectively exert its modification effect, failing to effectively suppress volume expansion and thus having little impact on cycle performance. Conversely, if the coating layer thickness is too high, such as greater than 120 nm, the capacity, rate capability, and cycle performance will actually decrease. Therefore, the thickness of the second coating layer 30 needs to be set appropriately.

[0080] Optionally, the particle size D50 of the core sodium ion cathode material 10 is 0.5 μm to 10 μm. As an example, the particle size D50 of the core sodium ion cathode material 10 can be any one of 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm, or a range between any two. By controlling the particle size of the sodium ion cathode material 10 within the above range, the compaction density of the cathode material can be further improved while ensuring a high sodium ion transport rate.

[0081] [Preparation methods for cathode materials]

[0082] Accordingly, in some embodiments, a method for preparing a positive electrode material is provided, the method comprising the following steps:

[0083] Sodium-ion cathode material 10 is mixed with a silicon-containing compound, and an intermediate material is obtained after the reaction.

[0084] The intermediate material was sintered in the first stage to obtain sodium ion cathode material 10 coated with sodium silicate.

[0085] Sodium-ion cathode material 10 coated with sodium silicate is mixed with a bismuth-containing compound and sintered in a second stage. The sintering temperature of the first stage is lower than that of the second stage to obtain the cathode material.

[0086] The positive electrode material includes a core, a first coating layer 20 covering at least a portion of the surface of the core, and a second coating layer 30 covering at least a portion of the surface of the first coating layer 20; the core includes a sodium ion positive electrode material 10; the first coating layer 20 includes sodium silicate; and the second coating layer 30 includes bismuth silicate.

[0087] The method for preparing the cathode material provided by this invention utilizes the hydrolysis and condensation reaction of silicon-containing compounds (such as tetraethyl orthosilicate) and resin, and uses acidic bismuth nitrate to provide a catalytic environment to prepare a coating mixture using silicon and bismuth sources as raw materials. A dual-functional coating is achieved through temperature differences. The inner layer, i.e., the first coating layer 20, coats the surface of individual particles by consuming residual alkali on the particle surface. This not only consumes harmful substances (residual alkali) but also improves processing and storage, and enhances conductivity. The outer layer, i.e., the second coating layer 30, achieves a thin film coating effect at medium to high temperatures, thus achieving the coating effect on multiple particles, suppressing volume expansion, preventing lattice distortion that could cause microcracks in the stress bands within the particles, and also possessing high conductivity, improving kinetic performance. The presence of the dual-functional coating in this invention ensures interface stability, thereby achieving long-cycle performance. Particularly noteworthy is that, compared to existing methods for preparing multifunctional coatings, the process of this invention is simpler, conducive to large-scale production, and has good application prospects.

[0088] The preparation method provided in this invention is a method for preparing sodium-ion battery cathode materials with dual-functional coating surface modification. This process is simple, convenient to operate, highly feasible, and easy to industrialize. This method can prepare layered oxide cathode materials for sodium-ion batteries with dual-functional coatings, that is, cathode materials with multi-layered structures, exhibiting good structural stability, excellent conductivity, and good cycle stability.

[0089] It should be understood that all the characteristics and advantages described above regarding "cathode materials" also apply to the "preparation method of cathode materials," and will not be repeated here.

[0090] In some feasible embodiments, the preparation of the layered oxide cathode material for sodium-ion batteries with dual-function coating of this application can be achieved by preparing a coating precursor material. During the sintering stage, by controlling the temperature difference, part of the silicon source material reacts with the material surface to produce a sodium silicate coating, and the other part reacts with bismuth nitrate to produce a bismuth silicate coating.

[0091] In some specific embodiments, the preparation method of the cathode material (such as a sodium-ion battery layered oxide cathode material with a dual-functional coating surface modification) specifically includes the following steps (a) to (c):

[0092] (a) Preparation of sodium ion cathode material.

[0093] In step (a), the preparation of sodium ion cathode material includes: mixing sodium-containing compound and transition metal oxide by ball milling to obtain a mixed material, pre-sintering the mixed material at a temperature of 300℃~525℃ for 6h~10h, and then sintering it at a temperature of 525℃~600℃ for 10h~16h to obtain sodium ion cathode material.

[0094] Optionally, the sodium-containing compound includes, but is not limited to, one or more of sodium carbonate (Na₂CO₃), sodium bicarbonate (NaHCO₃), or sodium hydroxide (NaOH). Preferably, the sodium-containing compound is selected from sodium carbonate. In this application, considering factors such as raw material availability and application effects, the use of sodium carbonate is more preferred.

[0095] Optionally, the transition metal oxide may include one or more of the following: oxides of Ni, Co, Mn, Cu, Fe, or Ti. Preferably, the transition metal oxide includes oxides of Ni (NiO) and oxides of Mn (MnO2).

[0096] Furthermore, in other embodiments, the sodium-containing compounds and transition metal oxides are not limited to the types listed above. Other types of sodium-containing compounds and transition metal oxides can be used to meet the requirements of excellent performance of the obtained cathode material, which will not be described in detail here.

[0097] Optionally, the ball milling described above can be performed using dry ball milling or wet ball milling, with graphite ball milling being preferred. For example, ethanol dispersant can be used for wet ball milling.

[0098] As an example, the pre-sintering temperature is 300℃ to 525℃, for example, any value or any two values ​​among 300℃, 350℃, 400℃, 450℃, 500℃, and 525℃; the pre-sintering time is 6h to 10h, for example, any value or any two values ​​among 6h, 7h, 8h, 9h, and 10h. The sintering temperature is 525℃ to 600℃, for example, any value or any two values ​​among 525℃, 550℃, 560℃, 580℃, and 600℃; the sintering time is 10h to 16h, for example, any value or any two values ​​among 10h, 11h, 12h, 13h, 14h, 15h, and 16h.

[0099] By controlling the pre-sintering conditions, sintering temperature, and time during the preparation of the above-mentioned sodium ion cathode material, it is helpful to obtain sodium ion cathode materials with excellent performance and further improve the electrochemical performance of cathode material products.

[0100] As an example, in some implementations, step (a) includes:

[0101] Weigh out the corresponding Na₂CO₃, MnO₂, and NiO powders according to a stoichiometric ratio of 1–1.05:1:1, add ethanol dispersant, and place in a ball mill jar for wet ball milling. Transfer the thoroughly mixed powder to a muffle furnace. Pre-sinter at 300–525℃ for 8 hours, then raise the temperature to 525–600℃ and hold for 10–16 hours. After calcination, allow to cool naturally to room temperature, grind thoroughly, and sieve to obtain the sodium ion cathode material, i.e., NaNi. 0.5 Mn 0.5 The O2 cathode material is designated as material number 1.

[0102] (b) Preparation of sodium ion cathode material coated with sodium silicate.

[0103] In step (b), the preparation of sodium silicate-coated sodium ion cathode material includes: mixing the sodium ion cathode material obtained in step (a) with a silicon-containing compound, reacting to obtain an intermediate material; and performing a first-stage sintering on the intermediate material to obtain sodium silicate-coated sodium ion cathode material.

[0104] Specifically, a silicon-containing compound and a resin are mixed, the pH is adjusted, and the mixture is heated and stirred. After separation, washing, and drying, a coated precursor material is obtained. The sodium-ion cathode material obtained in step (a), the coated precursor material, and a complexing agent are mixed, reacted, washed, and dried to obtain an intermediate material. The intermediate material is then subjected to a first-stage sintering process to obtain a sodium-ion cathode material coated with sodium silicate.

[0105] Optionally, the silicon-containing compound includes one or more of tetraethyl orthosilicate, methyl orthosilicate, or isopropyl orthosilicate. Preferably, the silicon-containing compound is selected from tetraethyl orthosilicate (TEOS).

[0106] Alternatively, in some embodiments, the silicon-containing compound may also be nano-silica.

[0107] In this application, silicon-containing compounds such as tetraethyl orthosilicate can play at least two roles. For example, one role is to form nano-silica, which reacts with residual alkali on the material surface to generate sodium silicate; the other role is to form precursor gel powder of unsintered bismuth silicate (Bi2SiO5).

[0108] Furthermore, in the preparation of cathode materials with dual-functional coating surface modification, the generated nanoparticle silica will adhere to the surface of the cathode material (sometimes it may not, sometimes it may not), and another type of sintered Bi2SiO5 precursor gel powder will also adhere to the surface of the cathode material. Due to the agglomeration of nanoparticles, they will attract the agglomeration of cathode material particles, and the complexing agent will also cause agglomeration. On the other hand, it will also cause the unsintered Bi2SiO5 precursor gel powder to bind to the surface of the cathode material.

[0109] Optionally, the resin is selected from phenolic resin.

[0110] Optionally, the volume ratio of the silicon-containing compound to the resin is 1:1 to 1:10; preferably, the volume ratio of the silicon-containing compound to the resin is 1:2. As examples, the volume ratios of the silicon-containing compound to the resin are 1:1, 1:2, 1:3, 1:4, 1:5, 1:8, 1:10, etc.

[0111] If the volume ratio of silicon-containing compounds to resin is too small, the hydrolysis will be incomplete, resulting in less silicon dioxide. If the ratio of silicon-containing compounds is too large, the hydrolysis process will be slow, reducing efficiency, and excess resin will also be wasted.

[0112] Optionally, pH adjustment includes adjusting the pH value to 3-5 using an acid solution; for example, adjusting the pH value to 3, 4, or 5. The acid solution can be any conventional acid in the art, such as hydrochloric acid, nitric acid, or acetic acid, and this application does not limit its use.

[0113] Optionally, the heating temperature for heating and stirring is 50℃~70℃, preferably 60℃, and the heating and stirring time is 6h~8h; as an example, the heating temperature can be any one of 50℃, 55℃, 60℃, 65℃, 70℃ or any range between two; the heating time can be any one of 6h, 7h, 8h or any range between two.

[0114] The above heating can be performed using water bath, oil bath, or other heating methods, with water bath being the preferred method.

[0115] Optionally, the separation in the above separation, washing and drying process can be carried out by centrifugation, the washing can be carried out by alcohols such as ethanol, and the drying can be carried out by freeze drying.

[0116] Optionally, the complexing agent includes, but is not limited to, any one or a combination of at least two of citric acid, tartaric acid, maleic acid, oxalic acid, or ethanolamine. Preferably, the complexing agent is selected from citric acid.

[0117] In this application, the main purpose of adding a complexing agent is to enhance the binding ability. At high temperatures, it can also increase the thermal motion of molecules, making the collisions between the complexing agent and the particles more frequent, thereby enhancing their binding ability.

[0118] Optionally, the mixing speed of the sodium-ion cathode material, the coating precursor material, and the complexing agent is 400–600 r / min, and the mixing time is 10–60 min. As an example, the mixing speed can be 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, etc., and the mixing time can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, etc.

[0119] Optionally, the sodium-ion cathode material, the coating precursor material, and the complexing agent are mixed, and the reaction temperature is 80℃~100℃, and the reaction time is 3h~5h. As an example, the reaction temperature can be any one of 80℃, 85℃, 90℃, 95℃, and 100℃, or any range between two; the reaction time can be any one of 3h, 4h, and 5h, or any range between two.

[0120] Optionally, the sodium ion cathode material, the coating precursor material, and the complexing agent are mixed and reacted, followed by washing and drying. The washing can be performed by washing with alcohol and water multiple times, and the drying temperature can be 55℃ to 65℃. As an example, the drying temperature can be any one of 55℃, 60℃, and 65℃, or any range between two of them.

[0121] Optionally, the sintering temperature for the first stage of sintering is 450℃ to 525℃. As an example, the sintering temperature can be any one of 450℃, 460℃, 480℃, 500℃, and 525℃, or a range between any two.

[0122] Optionally, the holding time for the first stage of sintering is 2h to 4h. As an example, the sintering time can be any one of 2h, 3h, and 4h, or a range between any two.

[0123] In the first sintering stage, some silicon dioxide can react with sodium carbonate, a residual alkali on the surface of the sodium ion cathode material, to produce a sodium silicate coating. Since the amount of residual alkali on the surface is limited, once the reaction is complete, the remaining silicon dioxide will not react with it. Therefore, there will be a certain amount of silicon dioxide remaining.

[0124] As an example, in some implementations, step (b) includes:

[0125] The silicon-containing compound and resin are mixed in a volume ratio of 1:1 to 1:10, for example, 5 mL of tetraethyl orthosilicate (TEOS) is mixed with 10 mL of phenolic resin to form a mixed solution. The pH is then adjusted to 3–5, and the mixture is magnetically stirred and refluxed in a water bath at 50–70°C (e.g., 60°C) for 6–8 hours. After the reaction system cools to room temperature, the product is separated by centrifugation at 6000–8000 rpm for 5–10 minutes. The precipitated product is washed with ethanol and freeze-dried to obtain a powdered coated precursor material. The reaction equations involved in this process are as follows:

[0126] Si(OCH2CH3)4+2H2O=SiO2+4C2H5OH.

[0127] Then, the sodium ion cathode material and the coating precursor material are first mixed to form a mixture, and then a complexing agent such as citric acid is added. The mixture is stirred at 400-600 r / min for 10 min-60 min (e.g., 30 min). The mixture is then transferred to a reaction vessel and reacted at 80℃-100℃ for 3-5 h. The collected product is washed three times with deionized water and ethanol, and dried at 55-65℃ to obtain the intermediate material.

[0128] Then, the intermediate material is placed in a crucible and placed in a muffle furnace for the first stage of sintering. The temperature of the first stage of sintering is slowly raised to 450℃~525℃ and held for 2h~4h to obtain sodium ion cathode material coated with sodium silicate.

[0129] (c) Preparation of cathode materials.

[0130] In step (c), the preparation of the cathode material includes: mixing sodium ion cathode material coated with sodium silicate with a bismuth-containing compound, and performing a second-stage sintering, wherein the sintering temperature of the first-stage sintering is lower than the sintering temperature of the second-stage sintering, thereby obtaining the cathode material.

[0131] In the process of forming the double-layer coating, this application mainly controls the reaction process by temperature difference. In the first stage of sintering, the temperature is first heated to 450℃~525℃, which is the temperature range in which silicon dioxide reacts with sodium carbonate to produce sodium silicate. Here, the surface particles will react with residual alkali to produce a sodium silicate substance. However, the residual alkali is limited, so the coating can be uniform or somewhat uneven and in small quantities. As the heating temperature increases, the precursor gel of unsintered Bi2SiO5 will generate another coating Bi2SiO5. By increasing the sintering temperature to 800℃~900℃ in the second stage of sintering, bismuth silicate is liquefied. The molten state of the liquefied bismuth silicate will cause the particles to fuse, forming a second coating film containing polymer particles.

[0132] Optionally, the bismuth-containing compound includes, but is not limited to, any one or a combination of at least two of bismuth nitrate, bismuth sulfate, bismuth chloride, bismuth acetate, or bismuth citrate. Preferably, the bismuth-containing compound is selected from bismuth nitrate.

[0133] Optionally, the molar ratio of the bismuth-containing compound to the silicon-containing compound is 1:1.5 to 1:4. As examples, the molar ratios of the bismuth-containing compound to the silicon-containing compound are 1:1.5, 1:2, 1:3, 1:4, etc.

[0134] Optionally, the sintering temperature for the second stage of sintering is 800℃ to 900℃. As an example, the sintering temperature can be any one of 800℃, 820℃, 850℃, 860℃, 880℃, or 900℃, or a range between any two.

[0135] Optionally, the holding time for the second stage sintering is 4h to 8h. As an example, the sintering time can be any one of 4h, 6h, and 8h, or a range between any two.

[0136] After the first stage of sintering, the second stage of sintering continues to heat up, such as to 800℃~900℃, and is held for 4h~8h, so that the remaining silicon dioxide reacts with the bismuth nitrate powder in the aforementioned material (the material that has been formed on the surface in the aforementioned steps) to generate a Bi2SiO5 bismuth silicate thin film coating; after grinding, drying and storage, the cathode material product is finally obtained.

[0137] In this application, the bismuth-containing compound is mixed by dropwise addition, such as adding the bismuth-containing compound solution dropwise to the above solution at a rate of 1 mL / min under magnetic stirring.

[0138] The preparation of the aforementioned double coating layer depends on the concentration and dropping rate of bismuth nitrate. The optimal dropping rate is 1 mL / min. If the dropping concentration is too low, excess silica may remain during sintering, potentially affecting capacity. If the dropping concentration is too high, excess bismuth nitrate will be loaded onto the particle surface, also affecting capacity utilization.

[0139] As an example, in some embodiments, step (c) includes: adding a bismuth-containing compound solution, such as a bismuth nitrate solution, dropwise to a sodium-ion cathode material coated with sodium silicate at a rate of 1 mL / min under magnetic stirring, and then performing a second-stage sintering in a muffle furnace, wherein the temperature of the second-stage sintering is raised to 800°C to 900°C and the holding time is 4 h to 8 h, to obtain the cathode material.

[0140] In other embodiments, tetraethyl orthosilicate and bismuth nitrate pentahydrate are used as raw materials, mixed in a ratio of nBi:nSi of 1:2, stirred and sonicated to form a sol-gel, dried and calcined at 650°C for 2 hours to obtain pure Bi2SiO5 powder.

[0141] It should be noted that the double-layer coating method of this application can achieve two effects through silicon-containing compounds such as tetraethyl orthosilicate: one effect is to form nano-silica; the other effect is to form unsintered bismuth silicate (B). i2 SiO5) precursor gel powder.

[0142] The generated nanoparticles of silica may or may not adhere to the surface of the cathode material. Another type of sintered Bi₂SiO₅ precursor gel powder also adheres to the cathode material surface. Because nanoparticles tend to aggregate, they attract the aggregation of cathode material particles. The complexing agent also contributes to aggregation. On the other hand, it allows the unsintered Bi₂SiO₅ precursor gel powder to bind to the surface of the cathode material.

[0143] Furthermore, the reaction process is controlled by temperature differences. In the first stage of sintering, the temperature is first heated to 450℃~525℃, which is the temperature range in which silicon dioxide reacts with sodium carbonate to produce sodium silicate. Here, the surface particles will react with residual alkali to produce a sodium silicate substance. However, the residual alkali is limited, so the coating can be uniform or somewhat uneven and in small quantities. As the heating temperature increases, the precursor gel of unsintered Bi2SiO5 will generate another coating Bi2SiO5. By increasing the sintering temperature to 800℃~900℃ in the second stage of sintering, bismuth silicate is liquefied. The molten state of the liquefied bismuth silicate will cause the particles to fuse, forming a second coating film containing polymer particles.

[0144] The method of adding the bismuth-containing compound is not limited to the above method. For example, the bismuth-containing compound can be added in step (c) or in step (b).

[0145] Therefore, based on the above setup, this application utilizes the hydrolysis and condensation reaction of silicon-containing compounds such as tetraethyl orthosilicate and resin, and provides an acidic bismuth nitrate catalytic environment to prepare a coating layer mixture using silicon and bismuth sources as raw materials. A dual-functional coating is achieved through temperature differences. The inner layer, i.e., the first coating layer 20, enhances conductivity by consuming residual alkali on the particle surface to coat the surface of individual particles. The outer layer, i.e., the second coating layer 30, achieves a thin-film coating effect on multiple particles through medium to high temperatures, suppressing volume expansion. The method of this invention synthesizes a high-performance sodium-ion battery cathode material with a coating having an ion-conducting layer. From the perspective of design concept and large-scale process feasibility, this material exhibits excellent electrochemical performance.

[0146] This invention forms a double-layered, uniform, and stable protective coating on the surface of a layered oxide cathode material for sodium-ion batteries through a simple surface modification method. The first layer is a sodium silicate ion-conducting layer, and the first coating layer 20 coats the surface of the material particles. The second coating layer 30 is a bismuth silicate layer with thin film properties, which coats the aggregates between particles.

[0147] This invention utilizes a stepwise calcination method to prepare composite precursors. It leverages the acidic catalysis of bismuth-containing compound solutions, such as bismuth nitrate solutions, to hydrolyze and polymerize silicon-containing compounds, such as tetraethyl orthosilicate. This eliminates the need for additional acidic substances to regulate the pH during hydrolysis. Excessive alkalinity may lead to colloidal polymerization, and the acidic concentration of bismuth nitrate will also decrease. This method offers green benefits for subsequent sintering processes.

[0148] The method of the present invention utilizes the temperature difference between medium and high temperature and the heating to make part of the coating precursor containing SiO2 and bismuth nitrate react with sodium carbonate in residual alkali and part of it react with bismuth nitrate to produce bismuth silicate, thereby achieving a dual-functional coating through a one-step heating method.

[0149] In the cathode material prepared by the method of the present invention, the first coating layer 20 is a sodium silicate ion conductor coating formed by reacting with residual alkali on the surface of the sodium-ion battery cathode material, and the second coating layer 30 is a bismuth silicate coating. This first coating layer can be a sodium silicate coating formed by reacting residual alkali on the surface of the sodium-ion cathode material with silicon material. This not only reduces residual alkali on the material surface and lowers the pH, improving subsequent processing problems caused by high pH, ​​but also provides excellent protection or improvement for the core sodium-ion cathode material. Furthermore, sodium silicate has a certain conductivity (10⁻⁶). -6 S.cm -1This enhances the conductivity of the cathode material. Furthermore, the second coating layer is a bismuth silicate coating, which protects both the core sodium-ion cathode material and the first coating layer. In particular, the bismuth silicate coating has a large specific surface area, providing not only active sites and improving electrochemical activity, but also a certain degree of flexibility (e.g., bismuth silicate with thin-film properties). The presence of bismuth silicate minimizes volume expansion during sodium ion insertion and extraction, reducing internal stress and preventing microcracks in the particles, thus ensuring particle integrity and cycle performance.

[0150] [Positive electrode tablets]

[0151] In some embodiments, this application provides a positive electrode sheet, which includes a current collector and a positive electrode active material layer disposed on the surface of the current collector; the positive electrode active material layer includes the aforementioned positive electrode material, or includes the positive electrode material prepared by the aforementioned method.

[0152] The positive electrode includes the positive electrode material described above in the embodiments of this application, and therefore, the positive electrode also has the characteristics of excellent electrochemical performance.

[0153] This application does not impose any particular restrictions on the material of the positive electrode current collector, as long as it can achieve the purpose of this application, and can be selected according to actual needs. For example, the positive electrode current collector can be a metal foil or a composite current collector. For example, the positive electrode current collector can contain aluminum foil or aluminum alloy foil. Of course, in other embodiments, composite current collectors (such as aluminum-carbon composite current collectors) can also be used.

[0154] In some embodiments, the positive electrode active material layer includes the positive electrode material described above provided in this application. Further, the positive electrode active material layer may optionally include a conductive agent. Further, the positive electrode active material layer may optionally include a binder.

[0155] This application does not impose any particular limitation on the types of conductive agents and binders in the positive electrode active material layer, as long as they can achieve the purpose of this application. For example, the binder may include, but is not limited to, one or more of polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene-butadiene copolymer (styrene-butadiene rubber), polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, or sodium carboxymethyl cellulose. The conductive agent may include, but is not limited to, at least one of conductive carbon black, carbon nanotubes, carbon fibers, Ketjen black, graphene, or conductive polymers.

[0156] This application does not impose any particular restrictions on the mass ratio of the positive electrode material, conductive agent, and binder in the positive electrode active material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.

[0157] This application does not impose any particular limitation on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the purpose of this application can be achieved. For example, the thickness of the positive electrode current collector can be 6 μm to 20 μm, and the thickness of the positive electrode active material layer can be 20 μm to 100 μm. This application does not impose any particular limitation on the thickness of the positive electrode sheet, as long as the purpose of this application can be achieved, for example, the thickness of the positive electrode sheet can be 30 μm to 200 μm.

[0158] This application does not impose any particular limitation on the preparation method of the positive electrode sheet; any preparation method known in the art can be used, as long as it can achieve the purpose of this application. As an example, in specific implementation, the above-mentioned positive electrode material can be stirred evenly with a conductive agent, a binder, and a solvent, and then processed into a positive electrode sheet through processes such as coating, rolling, slitting, and cutting.

[0159] [Battery]

[0160] In some embodiments, this application provides a battery that includes the aforementioned positive electrode and negative electrode.

[0161] The battery includes the positive electrode material provided in the embodiments of this application. Therefore, the battery, such as a sodium-ion secondary battery, also has excellent electrochemical performance, such as long cycle life, good conductivity and high capacity.

[0162] The aforementioned battery also includes an electrolyte and a separator.

[0163] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer including a negative electrode material.

[0164] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0165] In this embodiment, the specific materials and structures of the negative current collector and the negative active material layer in the negative electrode sheet are not limited, and negative electrode sheet structures and compositions known in the art that can be used in secondary batteries can be selected.

[0166] This application does not impose any particular restrictions on the negative electrode current collector, as long as it can achieve the purpose of this application. For example, the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collectors, etc.

[0167] The negative electrode active material layer in this application includes not only the negative electrode material but may also include conductive agents, binders, or optional thickeners. The negative electrode material in this application may include at least one of the following: metal oxides, metal sulfides, metal phosphides, Sb-based negative electrode materials, hard carbon, soft carbon, and metallic sodium. The aforementioned metal oxides may include, for example, one or more of cobalt oxide, iron oxide, nickel oxide, and copper oxide. Metal sulfides may include, for example, one or more of tungsten disulfide, molybdenum disulfide, and tin disulfide. Metal phosphides may include, for example, one or more of lithium phosphide and sodium phosphide. Sb-based negative electrode materials may include, for example, at least one of Sb-C composite materials, NiSb alloys, and Sb₂O₃.

[0168] The embodiments of this application do not have any particular restrictions on the types of conductive agents, binders, thickeners, etc. in the negative electrode active material layer, as long as they can achieve the purpose of this application, and will not be described in detail here.

[0169] In this application, there are no particular limitations on the thickness of the negative electrode current collector and the negative electrode active material layer, as long as the purpose of this application can be achieved. For example, the thickness of the negative electrode current collector is 5 μm to 20 μm, and the thickness of the negative electrode active material layer is 20 μm to 150 μm. In this application, there are no particular limitations on the thickness of the negative electrode sheet, as long as the purpose of this application can be achieved, for example, the thickness of the negative electrode sheet is 20 μm to 200 μm.

[0170] This application does not impose any particular restrictions on the separator, as long as it can achieve the purpose of this application. For example, the material of the separator may include, but is not limited to, at least one of polyethylene (PE), polyolefin (PO) based on polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid, or the separator may also be selected from glass fiber, non-woven fabric, etc.

[0171] In this application, the sodium-ion battery also includes an electrolyte, which comprises a sodium salt and a non-aqueous organic solvent. This application does not impose any particular limitation on the type of sodium salt or its concentration in the electrolyte, as long as the purpose of this application is achieved. As an example, the sodium salt may include, but is not limited to, at least one of NaPF6, NaOTF, NaFSI, NaTFSI, NaBF4, NaDFOB, NaBOB, and NaClO4. The concentration of the sodium salt in the electrolyte is from 0.9 mol / L to 2 mol / L.

[0172] This application does not impose any particular limitation on non-aqueous organic solvents, as long as they can achieve the purpose of this application. For example, they may include, but are not limited to, at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, or other organic solvents. As examples, carbonate compounds and carboxylic acid ester compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, and propyl propionate.

[0173] The battery of this application also includes a packaging shell for housing the positive electrode, separator, negative electrode, and electrolyte, as well as other components known in the art for sodium-ion batteries. This application does not limit the aforementioned other components. This application does not impose any particular limitation on the packaging shell; it can be a packaging shell known in the art, as long as it can achieve the purpose of this application.

[0174] This invention does not impose any special restrictions on the battery preparation method; any technical solution known to those skilled in the art for preparing a battery, such as a secondary battery, from a positive electrode material can be used.

[0175] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0176] Example 1

[0177] The preparation of the cathode material includes the following steps:

[0178] (1) Weigh the corresponding Na₂CO₃, MnO₂, and NiO powders according to a stoichiometric ratio of 1:1:1, add ethanol dispersant, and place in a ball mill jar for wet ball milling. Transfer the thoroughly mixed powder to a muffle furnace. First, pre-sinter at 500℃ for 8 hours, then raise the temperature to 600℃ and hold for 16 hours. After calcination, allow it to cool naturally to room temperature, grind thoroughly, and sieve to obtain the sodium ion cathode material, i.e., NaNi. 0.5 Mn 0.5 The O2 cathode material is designated as material number 1.

[0179] (2) Mix 10 mL of tetraethyl orthosilicate (TEOS) with 10 mL of phenolic resin to form solution A. Then adjust the pH to 5, and hydrolyze under reflux with magnetic stirring at 60 °C in a water bath for 8 h. After the reaction system cools to room temperature, centrifuge at 8000 r / min for 10 min to separate the product. Wash the precipitate with ethanol, freeze-dry it to obtain a powdered coated precursor material, designated as material No. 2.

[0180] (3) Mix the powder of material No. 2 and material No. 1 to prepare a mixture, then add citric acid as a complexing agent and stir at 600 r / min for 0.5 h; then transfer the mixture to a reaction vessel and react at 100 °C for 5 h. Wash the collected product three times with deionized water and ethanol respectively, and dry at 60 °C to obtain material No. 3.

[0181] (4) After mixing material No. 3 evenly, put it into a crucible and place it in a muffle furnace for the first stage of sintering. The temperature of the first stage of sintering is first slowly raised to 500℃ and held for 4 hours to obtain sodium ion cathode material coated with sodium silicate.

[0182] (5) Bismuth nitrate solution was added dropwise to sodium ion cathode material coated with sodium silicate at a rate of 1 mL / min under magnetic stirring. Then, a second-stage sintering was carried out in a muffle furnace, with the temperature raised to 900℃ and held for 6 h to synthesize a Bi2SiO5 bismuth silicate thin film coating. After grinding, drying and storage, the cathode material was finally obtained, such as Bi2SiO5@Na2SiO3@NaNi. 0.5 Mn 0.5 O2.

[0183] Example 2

[0184] Example 2 is basically the same as Example 1, except that:

[0185] In step (2), 5 mL of tetraethyl orthosilicate (TEOS) and 10 mL of phenolic resin were mixed to form solution A. The pH was then adjusted to 5, and the mixture was magnetically stirred and refluxed in a water bath at 60°C for 8 hours to hydrolyze the product. After the reaction system cooled to room temperature, the product was separated by centrifugation at 8000 r / min for 10 minutes. The precipitated product was washed with ethanol and freeze-dried to obtain a powdered coated precursor material, designated as material No. 2.

[0186] Everything else is the same as in Example 1.

[0187] Example 3

[0188] Example 3 is basically the same as Example 1, except that:

[0189] In step (2), 1 ml of tetraethyl orthosilicate (TEOS) and 10 ml of phenolic resin were mixed to form solution A. The pH was then adjusted to 5, and the mixture was magnetically stirred and refluxed in a water bath at 60°C for 8 hours to hydrolyze the product. After the reaction system cooled to room temperature, the product was separated by centrifugation at 8000 r / min for 10 minutes. The precipitated product was washed with ethanol and freeze-dried to obtain a powdered coated precursor material, designated as material No. 2.

[0190] Everything else is the same as in Example 1.

[0191] The main difference between Examples 2 and 3 is the amount of tetraethyl orthosilicate (TEOS), a silicon-containing compound, used to change the amount of coating in the first coating layer.

[0192] Example 4

[0193] Example 4 is basically the same as Example 1, except that:

[0194] In step (2), 10 mL of tetraethyl orthosilicate (TEOS) and 10 mL of phenolic resin were mixed to form solution A. The pH was then adjusted to 4, and the mixture was refluxed under magnetic stirring at 60°C in a water bath for 8 hours. After the reaction system cooled to room temperature, the product was separated by centrifugation at 8000 r / min for 10 minutes. The precipitated product was washed with ethanol and freeze-dried to obtain a powdered coated precursor material, designated as material No. 2.

[0195] Everything else is the same as in Example 1.

[0196] Example 5

[0197] Example 5 is basically the same as Example 1, except that:

[0198] In step (2), 10 mL of tetraethyl orthosilicate (TEOS) and 10 mL of phenolic resin were mixed to form solution A. The pH was then adjusted to 6, and the mixture was refluxed under magnetic stirring at 60°C in a water bath for 8 hours. After the reaction system cooled to room temperature, the product was separated by centrifugation at 8000 rpm for 10 minutes. The precipitated product was washed with ethanol and freeze-dried to obtain a powdered coated precursor material, designated as material No. 2.

[0199] Everything else is the same as in Example 1.

[0200] The above-described Examples 4 and 5 mainly change the coating amount of the second coating layer by adjusting the pH of the control system.

[0201] Example 6

[0202] Example 6 is basically the same as Example 1, except that:

[0203] In step (2), 10 mL of tetraethyl orthosilicate (TEOS) and 10 mL of phenolic resin were mixed to form solution A. The pH was then adjusted to 6, and the mixture was refluxed under magnetic stirring at 60°C in a water bath for 8 hours. After the reaction system cooled to room temperature, the product was separated by centrifugation at 8000 rpm for 10 minutes. The precipitated product was washed with ethanol and freeze-dried to obtain a powdered coated precursor material, designated as material No. 2.

[0204] In step (4), after the No. 3 material is mixed evenly, it is placed in a crucible and placed in a muffle furnace for the first stage of sintering. The temperature of the first stage of sintering is first slowly raised to 400℃ and held for 4 hours to obtain sodium ion cathode material coated with sodium silicate.

[0205] Everything else is the same as in Example 1.

[0206] The above implementation 6 mainly changed the temperature of the first stage sintering in order to examine the effect of the first stage sintering temperature on the uniformity of the first coating layer, or whether the temperature is sufficient.

[0207] Example 7

[0208] Example 7 is basically the same as Example 1, except that:

[0209] In step (2), 10 mL of tetraethyl orthosilicate (TEOS) and 10 mL of phenolic resin were mixed to form solution A. The pH was then adjusted to 5, and the mixture was refluxed under magnetic stirring at 60°C in a water bath for 8 hours. After the reaction system cooled to room temperature, the product was separated by centrifugation at 8000 r / min for 10 minutes. The precipitated product was washed with ethanol and freeze-dried to obtain a powdered coated precursor material, designated as material No. 2.

[0210] In step (5), bismuth nitrate solution was added dropwise to sodium ion cathode material coated with sodium silicate at a rate of 1 mL / min under magnetic stirring. Then, a second-stage sintering was carried out in a muffle furnace, with the temperature raised to 800℃ and held for 6 h to synthesize a Bi2SiO5 bismuth silicate thin film coating. After grinding, drying and storage, the cathode material was finally obtained, such as Bi2SiO5@Na2SiO3@NaNi. 0.5 Mn 0.5 O2.

[0211] Everything else is the same as in Example 1.

[0212] The above embodiment 7 mainly changed the sintering temperature of the second stage to examine the effect of the sintering temperature of the second stage on the uniformity of the second coating layer.

[0213] Comparative Example 1

[0214] The preparation of the cathode material includes the following steps:

[0215] (1) Weigh the corresponding Na₂CO₃, MnO₂, and NiO powders according to a stoichiometric ratio of 1:1:1, add ethanol dispersant, and place in a ball mill jar for wet ball milling. Transfer the thoroughly mixed powder to a muffle furnace. Pre-sinter at 500℃ for 8 hours, then raise the temperature to 900℃ and hold for 16 hours. After calcination, allow to cool naturally to room temperature, grind thoroughly, and sieve to obtain NaNi. 0.5 Mn 0.5 The O2 cathode material is designated as material number 1.

[0216] (2) Mix 5 ml of tetraethyl orthosilicate (TEOS) with 10 ml of phenolic resin to form solution A; hydrolyze by magnetic stirring under reflux at 60 °C in a water bath for 8 h; after the reaction system is cooled to room temperature, centrifuge at 8000 r / min for 10 min to separate the product; wash the precipitate with ethanol, freeze dry to obtain powdered silica material, which is designated as material No. 2.

[0217] (3) Mix the powder of material No. 2 and material No. 1 to prepare a mixture, and stir at 600 r / min for 0.5 h; then transfer the mixture to the reaction vessel and react at 100 °C for 5 h. Wash the collected product three times with deionized water and ethanol respectively, and dry at 60 °C to obtain material No. 3.

[0218] (4) After mixing material No. 3 evenly, place it in a crucible and put it in a muffle furnace. First, slowly heat it to 500℃ and hold it at that temperature for 4 hours. After grinding, dry and store it to finally obtain the cathode material Na2SiO3@NaNi. 0.5 Mn 0.5 O2.

[0219] In the preparation of the cathode material in Comparative Example 1, only sodium silicate coating was applied, and the sintering temperature was controlled at 500℃.

[0220] Comparative Example 2

[0221] The preparation of the cathode material includes the following steps:

[0222] (1) Weigh the corresponding Na₂CO₃, MnO₂, and NiO powders according to a stoichiometric ratio of 1:1:1, add ethanol dispersant, and place in a ball mill jar for wet ball milling. Transfer the thoroughly mixed powder to a muffle furnace. Pre-sinter at 500℃ for 8 hours, then raise the temperature to 900℃ and hold for 16 hours. After calcination, allow to cool naturally to room temperature, grind thoroughly, and sieve to obtain NaNi. 0.5 Mn 0.5 The O2 cathode material is designated as material number 1.

[0223] (2) Bismuth nitrate solution was added dropwise to ethanol solution at a rate of 1 mL / min under magnetic stirring. Citric acid was added as a complexing agent. The mixture was then refluxed under magnetic stirring in a water bath at 60°C for 8 h. After the reaction system cooled to room temperature, the product was separated by centrifugation at 6000 r / min for 10 min. The precipitate was washed with ethanol and freeze-dried to obtain the bismuth nitrate coated precursor material, designated as material No. 2.

[0224] (3) Mix the powder of material No. 2 and material No. 1 to prepare a mixture, and stir at 600 r / min for 0.5 h; then transfer the mixture to the reaction vessel and react at 100 °C for 5 h. Wash the collected product three times with deionized water and ethanol respectively, and dry at 60 °C to obtain material No. 3.

[0225] (4) After mixing material No. 3 evenly, place it in a crucible, put it in a muffle furnace, heat it to 600℃ and hold it for 6 hours, grind it, dry and store it to finally obtain the cathode material Bi2SiO5@NaNi. 0.5 Mn 0.5 O2.

[0226] In the preparation of the cathode material in Comparative Example 2, only a bismuth silicate coating was applied, and the sintering temperature was controlled at 600℃.

[0227] Comparative Example 3

[0228] The preparation of the cathode material includes the following steps:

[0229] (1) Weigh the corresponding Na₂CO₃, MnO₂, and NiO powders according to a stoichiometric ratio of 1:1:1, add ethanol dispersant, and place in a ball mill jar for wet ball milling. Transfer the thoroughly mixed powder to a muffle furnace. Pre-sinter at 500℃ for 8 hours, then raise the temperature to 900℃ and hold for 16 hours. After calcination, allow to cool naturally to room temperature, grind thoroughly, and sieve to obtain NaNi. 0.5 Mn 0.5 The O2 cathode material is designated as material number 1.

[0230] (2) Mix 10 mL of tetraethyl orthosilicate (TEOS) with 10 mL of phenolic resin to form solution A. Then, under magnetic stirring, add bismuth nitrate solution dropwise to solution A at a rate of 1 mL / min. Hydrolyze under reflux with magnetic stirring in a water bath at 60 °C for 8 h. After the reaction system cools to room temperature, centrifuge at 8000 r / min for 10 min to separate the product. Wash the precipitate with ethanol and freeze-dry to obtain powdered silica / bismuth nitrate coated precursor material, designated as material No. 2.

[0231] (3) Mix material No. 2 and material No. 1 powder by ball milling for 3 hours at a speed of 400 r / min. After mixing, material No. 3 is obtained.

[0232] (4) After mixing material No. 3 evenly, place it in a crucible and put it in a muffle furnace. For the first stage, slowly heat the material to 500℃ and hold it for 4 hours. Then, continue to heat the material to 600℃ and hold it for 6 hours. After grinding, dry and store the material to obtain the cathode material Bi2SiO5@Na2SiO3@NaNi. 0.5 Mn 0.5 O2.

[0233] In the preparation of the cathode material in Comparative Example 3, the powder was directly ball-milled and mixed without adding a complexing agent and undergoing hydrothermal treatment.

[0234] Performance testing

[0235] The cathode materials of the above embodiments and comparative examples were applied to batteries, and the battery capacity and cycle performance were tested.

[0236] 1. Prepare the battery according to the following steps:

[0237] Preparation of positive electrode sheet: The positive electrode material is mixed with the binder polyvinylidene fluoride and the conductive agent conductive carbon black SP in a ratio of 8:1:1. N-methylpyrrolidone (NMP) solvent is added and stirred thoroughly to form a uniform and stable slurry. The slurry is then coated on the current collector aluminum foil, dried, and cut to obtain the positive electrode sheet.

[0238] Preparation of negative electrode: Sodium metal sheet is used as negative electrode.

[0239] Battery assembly: In an argon glove box with oxygen <0.1ppm and water content <0.1ppm, a CR2032 button cell was assembled using a sodium metal sheet as the negative electrode, a glass fiber membrane as the separator, and NaPF6 dissolved in diethylene glycol dimethyl ether as the electrolyte.

[0240] 2. Performance Testing

[0241] The cathode materials and batteries prepared in the above embodiments and comparative examples were subjected to performance tests. The specific test methods are as follows:

[0242] (1) pH value test: 1g of the positive electrode material obtained in each of the above examples and comparative examples was dispersed in 20mL of deionized water and stirred at low speed for 1min. After stirring, it was allowed to stand for 3min. The pH value of the supernatant after standing was measured using a Mettler pH meter. The obtained pH value is the alkalinity of the obtained positive electrode material. After the treated positive electrode material was placed in the same environment for energy storage for one week, the pH value was tested again. The corresponding test results are shown in Table 1.

[0243] (2) Initial discharge capacity, initial charge capacity, and initial coulombic efficiency test: Under the temperature condition of 25℃, first discharge to 2V with constant current of 0.1C, let stand for 10min, then charge to 4.2V with constant current of 0.1C, and record the charging specific capacity at this time as the initial charge specific capacity. After standing for 10min, discharge to 2.0V with constant current of 0.1C, and record the discharge specific capacity at this time as the initial discharge specific capacity.

[0244] Initial coulombic efficiency = initial discharge specific capacity / initial charge specific capacity * 100%.

[0245] (3) Cycle capacity retention test: Under 25℃ temperature conditions, discharge at a constant current of 1C to 2V, let stand for 10 minutes, then charge at a constant current of 1C to 4.2V. The obtained charging value is the specific capacity of the first charge cycle. After letting stand for 10 minutes, discharge at a constant current of 1C to 2.0V, and record the obtained discharge value as the specific capacity of the first discharge cycle. This is one cycle. The capacity retention rate is = discharge capacity of the cycle / charge capacity of the cycle * 100%. The test is stopped when it reaches 50%.

[0246] The test results are shown in Table 2.

[0247] Table 1. pH test results for each example and comparative example.

[0248] Example 1 10.7 10.8 Example 2 11.0 11.2 Example 3 11.2 11.5 Example 4 10.8 10.9 Example 5 10.8 11.0 Example 6 11.3 11.6 Example 7 10.9 11.2 Comparative Example 1 11.4 11.9 Comparative Example 2 11.9 12.3 Comparative Example 3 11.5 11.8

[0249] Table 2. Battery performance test results for each embodiment and comparative example.

[0250]

[0251]

[0252] As can be seen from Tables 1 and 2, compared with Comparative Examples 1-3, the cathode materials of Examples 1-7 of the present invention can reduce the residual alkali on the material surface, thereby reducing the pH and improving subsequent processing problems caused by high pH. Furthermore, compared with Comparative Examples 1-2, batteries prepared using the cathode materials provided in Examples 1-7 have higher initial charge-discharge capacity, higher first-in-stock efficiency, and better cycle performance. This indicates that the cathode materials prepared in the embodiments of the present invention have significantly increased structural stability compared with existing materials. Therefore, utilizing the excellent structural stability of this cathode material can ensure particle integrity, thereby improving the electrochemical performance such as cycle stability.

[0253] Furthermore, as shown in Table 1, the cathode material of Example 1 achieved a better effect in reducing residual alkali. This is mainly because the initial residual alkali content on the surface is related to the sodium silicate content, which can react with the residual alkali and is the main factor affecting the initial synthesis pH. Bismuth silicate has a secondary effect; its main function is to inhibit volume expansion. At the same time, the coating layer isolates moisture in the air to prevent direct contact with the cathode material surface. Through a comprehensive comparison of Examples 1-7 and Comparative Examples 1-3, it can be seen that the initial pH and pH change of Examples 1-7 are lower than those of Comparative Examples 1-3, especially Example 1, which is more effective. Compared with Example 1, Examples 2-3 gradually reduced the content of silicon-containing compounds, thereby reducing the coating material of the first coating layer. Since this is the main factor affecting pH, the overall pH value is larger than that of Examples 4 and 5, which changed the coating of the second coating layer. From Examples 2 and 3, it can also be concluded that when the coating content of sodium silicate is reduced, the residual alkali on the surface is not completely reacted, resulting in a higher pH. Examples 4 and 5 primarily altered the coating content of the second coating layer. It was observed that a higher pH reduced the bismuth nitrate content, resulting in a smaller bismuth silicate coating layer. This could lead to uneven or insufficient formation of the subsequent second coating layer. Therefore, the pH value of Example 5 was slightly higher than that of Example 4. Examples 6 and 7 affected the reaction degree of the first and second coating layers, respectively, thus their impact on pH was higher than in Example 1 and other examples. Furthermore, considering Examples 1-7, it was found that the surface residual alkali was lowest when the ratio of sodium silicate coating to bismuth silicate coating was appropriate. Considering Comparative Examples 1-3, the effect of the absence of a sodium silicate coating layer on residual alkali was more significant in Comparative Example 1, with a greater change and initial pH value than in Comparative Example 2 without a bismuth silicate coating layer. Comparative Example 3 affected the bonding between coating layers; therefore, its impact on pH was less significant than that of Comparative Examples 1 and 2.

[0254] Table 2 shows that the higher the coating amount of the silicon source, the lower the initial discharge capacity, which in turn affects the initial coulombic efficiency. Overall, the initial coulombic efficiency is generally greater than 92%, which is consistent with the basic pattern of layered oxides. Regarding the cycle capacity retention, Comparative Example 3, due to the lack of coating pretreatment, suffers from poor adhesion between the coating and the substrate, as well as uneven coating uniformity, leading to localized coating failure. However, the capacity retention is still higher than that of Comparative Example 1. Comparative Example 1, lacking a bismuth silicate coating to suppress volume expansion, has a lower capacity retention. Furthermore, Examples 1-3 show that as the coating amount decreases, the initial capacity may be slightly higher, but the capacity retention will decrease slightly. Examples 4 and 5, compared to Examples 2 and 3, are morphologically particulate fusion, and their capacity performance may be slightly lower than Examples 2 and 3. However, Example 4 achieves a higher capacity retention, while Example 5, due to the smaller amount of bismuth silicate, has less significant suppression of volume expansion during cycling, resulting in a slightly lower capacity retention than Example 4. Examples 6 and 7 primarily affect the coating integrity of the first and second coating layers by influencing the calcination temperature. Comparative Examples 1 and 2 show that a single-layer coating is far from sufficient for capacity retention, offering only a limited effect and resulting in low capacity retention. Although Comparative Example 3 uses a double-layer coating, it lacks a complexing agent, leading to weak bonding between the coating layers and consequently low capacity retention during cycling. The reduced effectiveness of the double-layer coating negatively impacts capacity retention.

[0255] Therefore, this invention, through a rationally designed double-coating layer, not only consumes residual alkaline substances that are detrimental to processing and electrochemical performance, but also transforms them into an ion-conducting layer that facilitates ion transport. Simultaneously, it addresses the issue of the crystal exhibiting good electrical conductivity, while its excellent mechanical properties mitigate volume changes during cycling. Through reasonable process adjustments, it not only leverages the material's structural stability but also its high specific capacity, thereby improving the overall electrochemical performance of the battery.

[0256] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0257] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0258] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0259] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0260] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode material, characterized in that, The cathode material includes a core, a first coating layer covering at least a portion of the surface of the core, and a second coating layer covering at least a portion of the surface of the first coating layer; The core includes a sodium ion cathode material; The first coating layer includes sodium silicate; The sodium silicate is Na2SiO3; The second coating layer includes bismuth silicate; The bismuth silicate is Bi2SiO5; The second coating layer comprises a thin film of bismuth silicate.

2. The cathode material according to claim 1, characterized in that, The first coating layer comprises a plurality of granular sodium silicate.

3. The cathode material according to claim 1, characterized in that, The thickness of the first coating layer is 20 nm to 50 nm; and / or, The thickness of the second coating layer is 50nm to 120nm.

4. The cathode material according to any one of claims 1 to 3, characterized in that, The chemical formula of the sodium ion cathode material is Na. x TMO2,TM includes at least two of the transition metals Ni, Co, Mn, Cu, Fe or Ti, and 0.6≤x≤1.

5. A method for preparing a positive electrode material, characterized in that, Includes the following steps: Sodium-ion cathode material and silicon-containing compound are mixed and reacted to obtain intermediate material; The intermediate material is subjected to a first-stage sintering process to obtain a sodium-ion cathode material coated with Na2SiO3. The sodium-ion cathode material coated with sodium silicate is mixed with a bismuth-containing compound and then sintered in a second stage. The sintering temperature of the first stage is lower than that of the second stage to obtain the cathode material. The cathode material includes a core, a first coating layer covering at least a portion of the surface of the core, and a second coating layer covering at least a portion of the surface of the first coating layer; the core includes a sodium ion cathode material. The second coating layer comprises Bi2SiO5; The sintering temperature for the first stage of sintering is 450℃~525℃; The sintering temperature for the second stage of sintering is 800℃~900℃.

6. The method for preparing the cathode material according to claim 5, characterized in that, The holding time for the first stage of sintering is 2 hours to 4 hours; and / or, The holding time for the second stage of sintering is 4 to 8 hours.

7. The method for preparing the cathode material according to claim 5 or 6, characterized in that, The steps for obtaining the intermediate material specifically include: Provide sodium ion cathode materials; Silicon-containing compounds and resins are mixed, pH is adjusted, and then heated and stirred. After separation, washing and drying, the coated precursor material is obtained. The sodium ion cathode material, the coating precursor material, and the complexing agent are mixed, reacted, washed, and dried to obtain the intermediate material.

8. The method for preparing the cathode material according to claim 7, characterized in that, The preparation method satisfies at least one of the following features (1) to (11): (1) The sodium ion cathode material is provided by: mixing sodium-containing compound and transition metal oxide by ball milling to obtain a mixed material, pre-sintering the mixed material at a temperature of 300℃~525℃ for 6h~10h, and then sintering it at a temperature of 525℃~600℃ for 10h~16h to obtain the sodium ion cathode material; (2) The silicon-containing compound includes at least one of tetraethyl orthosilicate, methyl orthosilicate or isopropyl orthosilicate; (3) The resin includes phenolic resin; (4) The bismuth-containing compound includes at least one of bismuth nitrate, bismuth sulfate, bismuth chloride, bismuth acetate, or bismuth citrate; (5) The volume ratio of the silicon-containing compound to the resin is 1:1 to 1:10; (6) The molar ratio of the bismuth-containing compound to the silicon-containing compound is 1:1.5 to 1:4; (7) The pH adjustment includes adjusting the pH value to 3-5 using an acid solution; (8) The heating temperature for heating and stirring is 50℃~70℃, and the heating and stirring time is 6h~8h; (9) The complexing agent includes at least one of citric acid, tartaric acid, maleic acid, oxalic acid or ethanolamine; (10) The rotation speed when mixing the sodium ion cathode material, the coating precursor material and the complexing agent is 400-600 r / min and the mixing time is 10 min-60 min; (11) The reaction temperature is 80℃~100℃ and the reaction time is 3h~5h.

9. A positive electrode plate, characterized in that, It includes a current collector and a positive electrode active material layer disposed on the surface of the current collector; The positive electrode active material layer includes the positive electrode material as described in any one of claims 1 to 4, or includes the positive electrode material prepared by the method described in any one of claims 5 to 8.

10. A battery, characterized in that, It includes the negative electrode and the positive electrode as described in claim 9.

Citation Information

Patent Citations

  • Method for improving residual alkalinity on surface of ternary positive electrode material of lithium ion battery

    CN108878863A

  • Coating method for alkali reduction of ternary material

    CN112290014A

  • Bifunctional interface lithium ion battery nickel-rich single crystal positive electrode material and preparation method thereof

    CN112864372A

  • Battery pole piece, preparation method thereof and semi-solid lithium ion battery

    CN116093253A

  • Sodium-ion layered oxide positive electrode material coated with sodium silicate and preparation method of sodium-ion layered oxide positive electrode material

    CN119108530A